The Effect of Distance Learning With Learner Center Micro Teaching Model On Student’ Teaching Confidence and Teaching Skills - Adrianus Nasar; Melkyanus Bili Umbu Kaleka (JIPF (Jurnal Ilmu Pendidikan Fisika), 2020)
The purpose of this study is to find the effect of distance learning through learner center micro teaching model on students’ teaching confidence and teaching skills. The research design uses quasi-experimental research and pretest-posttest non controlled group design. The population is physics education students on sixth semester who was programming micro teaching courses. Purposes sampling technic used to get research sample and 31 students take part on this course. Data collected by using questionnaire on variables of teaching confidence and assessment rubric on variables of teaching skills. Teaching confidence and teaching skills are analyzed through normalized-gain and pair sample t-test. Data calculated use SPSS and the result is: 1) teaching confidence has normalized-gain <g> = 0,535 (moderate) and t = 12,336 (sig.=0,000); 2) teaching skills has normalized-gain <g> = 0,566 (moderate) dan t = 9,690 (sig.=0,000). The result shows the effect of distance learning through learner center micro teaching (LCMT) model can improve teaching confidence and teaching skills of physics education students on FKIP Universitas Flores.